Low-cost localization solution for underwater robot using single-beam SONAR and IMU - Loke, Wesley Ting Kai (Nanyang Technological University, 2024)
In this FYP, a closed loop control system was set up in order to control the movements of an Autonomous Underwater Vehicle (AUV). This takes inputs in the form of signals from inertial measurement units (IMU) as well as sonars, and passes them through a control loop system to determine errors and changes to displacement and velocity. To better control the AUV, Proportional-Integral-Derivative controllers are used. These controllers will calculate the error and determine the output. PID Tuning methods such as the Ziegler-Nichols Method and the Cohen-Coon open loop method were detailed and considered. To tune these controllers, the Ziegler-Nichols method will be used. The Ziegler-Nichols closed loop tuning method is a simple way of optimising control parameters.The movements covered are Surge, Sway and Yaw of the AUV, as these have been determined to be the most frequently changing in the context of open waters operation. Findings are detailed in the later chapters, alongside some graphs.